O empreendedorismo feminino contado em história de vida de mulheres empreendedoras parintinenses - Fernandes Neta, Celina Oliveira (BRASIL, 2023)
This research aimed to analyze the profiles and motivations of women entrepreneurs in Parintins and the obstacles faced by them when entering the market in Parintins through entrepreneurship. The investigation carried out sought to characterize the profile of women entrepreneurs in the city of Parintins/Amazonas; highlight the reasons that led them to undertake; and identify the obstacles faced in the management of projects. The scope of the research took place in the enterprises of four women entrepreneurs in the fields of beauty and aesthetics, costume jewelry, food and natural beauty in the city of Parintins. The methodological strategy was based on the Multiple Case Study. The study pointed out that women from Parintine have the ability to undertake, manage and grow their businesses with their own talents, especially if they have an academic background that supports the creation and development of their enterprises. He also pointed out that their motivations stem from the need for self-realization, family well-being and the pursuit of reputation, prestige, status, dominance, recognition, attention, importance or appreciation. The study also showed that in the management of their enterprises the oscillation of billing; the lack of qualified labor; reconciling the role of mother and entrepreneur; and the Covid-19 Pandemic were and still are the main obstacles faced by them with entrepreneurs.